3x-4=9x+28

Subtract 9x from both sides of the equation.

3x-4-9x=28

Subtract 9x from 3x.

-6x-4=28

-6x-4=28

Add 4 to both sides of the equation.

-6x=28+4

Add 28 and 4.

-6x=32

-6x=32

Divide each term in -6x=32 by -6.

-6x-6=32-6

Cancel the common factor of -6.

Cancel the common factor.

-6x-6=32-6

Divide x by 1.

x=32-6

x=32-6

Simplify 32-6.

Cancel the common factor of 32 and -6.

Factor 2 out of 32.

x=2(16)-6

Cancel the common factors.

Factor 2 out of -6.

x=2⋅162⋅-3

Cancel the common factor.

x=2⋅162⋅-3

Rewrite the expression.

x=16-3

x=16-3

x=16-3

Move the negative in front of the fraction.

x=-163

x=-163

x=-163

The result can be shown in multiple forms.

Exact Form:

x=-163

Decimal Form:

x=-5.3‾

Mixed Number Form:

x=-513

Solve for x 3x-4=9x+28